Story and Illustration Reconstituted: Children’s Literature in Canadian Reading Programs - Smith, Martha L.; Phillips, Linda M.; Leithead, Marion R.; Norris, Stephen P. (Alberta Journal of Educational Research, 2004)
This study addresses the differences between literature in children's trade books and the literature in commercial elementary language arts reading programs used in Canada. Although the nature of the literature included in language arts programs has received considerable scrutiny in the United States, there is no parallel body of research in the Canadian context. Using a textual content analysis, all the literature selections contained in the three most extensively used reading programs in Canada were where possible compared with the corresponding trade books. Numerous differences between trade book literature and the corresponding selections in the reading programs suggest that the two are not equivalent in the reading experiences they provide for children. The changes included alterations to format such as omissions, additions, substitutions, and reordering of text and illustrations. Many of the original selections reconstituted in the reading programs were impoverished by the changes. Further research is needed on how these changes alter children's reading experiences.